Literature Review: Karamunting (Rhodomyrtus Tomentosa Hask.) As A Cosmetic Agent - Paramawidhita, Risqika (Sciences and Clinical Pharmacy Research Journal, 2026)
This study aims to explore the potential of Rhodomyrtus tomentosa (Hask.), commonly known as karamunting, as a natural cosmetic agent through a qualitative-descriptive literature review. The research focuses on identifying the plant’s bioactive compounds, understanding their pharmacological activities, and evaluating their cosmetic relevance. Data were collected through an extensive review of peer-reviewed journals, scientific reports, and academic documents published between 2012 and 2025. The analysis involved thematic categorization and inductive interpretation of findings to derive meaningful insights into the plant’s functional roles in cosmetics. Results indicate that R. tomentosa contains diverse bioactive constituents—such as rhodomyrtone, flavonoids, phenolics, and triterpenoids—that exhibit strong antioxidant, antibacterial, anti-inflammatory, and skin-brightening properties. Advanced extraction methods, such as ultrasound-assisted extraction using eco-friendly solvents, have enhanced the yield and stability of active compounds, supporting sustainable cosmetic development. Clinical studies confirm its efficacy in acne treatment, comparable to conventional antibiotics, without adverse side effects. The findings reinforce theoretical models in phytocosmetics that emphasize the significance of natural plant-derived compounds in promoting skin health and sustainability. Overall, this study contributes to the advancement of natural cosmetology by integrating ethnobotanical knowledge with modern scientific validation and offers practical implications for future research and cosmetic formulation innovation.